Analysis of human resources readiness in facing natural disasters study case: Lapindo Sidoarjo mud disaster - Hussain, Adnan; Deviansari, Naza; Alamsyah , Rizal; Disrey, Inggrid; Ansori, Moch Fadil; Dhani , Ramdhani Amrullah (Calamity: A Journal of Disaster Technology and Engineering, 2024)
The Lapindo Mud Disaster is a phenomenon that occurs due to the overflow of mudflows emit from the malfunction of exploration by company, named PT. Minarak Lapindo Jaya, that occurred in Sidoarjo, East Java, Indonesia. So far, the efforts of the government and Lapindo have shown no success in stopping the flow or managing the social and environmental impacts of the overflowing mud. Until now, no less than 60.000 residents in the Tanggulangin, Porong, and Jabon sub- districts have been uprooted from the roots of their homeland. Sidoarjo, which is located between Surabaya and Gempol, is the main of East Java’s Transportation, which has an impact on economic losses in the macro and micro sectors. This study uses a descriptive research strategy, conduct by questioner to the refuges and analyze with Multiple Linear Regression Analysis. To determined which factors are significantly affect their livelihoods. But this is not necessarily felt by all residents, there are also those who are greatly disadvantaged because the main livelihood activities in the village/residence environment are disrupted.